The keeper of lost things : a novel - Hogan, Ruth, 1961- (William Morrow, an imprint of HarperCollinsPublishers, 2017)
Collecting things dropped or left behind by others and writing stories about them as a tribute to the fiancée who died the day he lost one of her keepsakes, a man bequeaths his estate to his unsuspecting assistant, who bonds with new neighbors while attempting to reunite the objects with their owners.